Freezing of Apheresis Platelet Concentrates in 6% Dimethyl Sulfoxide: The First Preliminary Study in Turkey - Soner Yılmaz; Rıza Aytaç Çetinkaya; İbrahim Eker; Aytekin Ünlü; Metin Uyanık; Serkan Tapan; Ahmet Pekoğlu; Aysel Pekel; Birgül Erkmen; Uğur Muşabak; Sebahattin Yılmaz; İsmail Yaşar Avcı; et al. (Turkish Journal of Hematology, 2016)
INTRODUCTION: Transfusion of platelet suspensions is an essential part of patient care for certain clinical indications. In this pioneering study in Turkey, we aimed to assess the in vitro hemostatic functions of platelets after cryopreservation. METHODS: Seven units of platelet concentrates were obtained by apheresis. Each apheresis platelet concentrate (APC) was divided into 2 equal volumes and frozen with 6% dimethyl sulfoxide (DMSO). The 14 frozen units of APCs were kept at -80 °C for 1 day. APCs were thawed at 37 °C and diluted either with autologous plasma or 0.9% NaCl. The volume and residual numbers of leukocytes and platelets were tested in both before-freezing and post-thawing periods. Aggregation and thrombin generation tests were used to analyze the in vitro hemostatic functions of platelets. Flow-cytometric analysis was used to assess the presence of frozen treated platelets and their viability. RESULTS: The residual number of leukocytes in both dilution groups was <1x106. The mean platelet recovery rate in the plasma-diluted group (88.1+-9.5%) was higher than that in the 0.9% NaCl-diluted group (63+-10%). These results were compatible with the European Directorate for the Quality of Medicines quality criteria. Expectedly, there was no aggregation response to platelet aggregation test. The mean thrombin generation potential of postthaw APCs was higher in the plasma-diluted group (2411 nmol/L per minute) when compared to both the 0.9% NaCl-diluted group (1913 nmol/L per minute) and the before-freezing period (1681 nmol/L per minute). The flowcytometric analysis results for the viability of APCs after cryopreservation were 94.9% and 96.6% in the plasma and 0.9% NaCl groups, respectively. DISCUSSION AND CONCLUSION: Cryopreservation of platelets with 6% DMSO and storage at -80 °C increases their shelf life from 7 days to 2 years. Besides the increase in hemostatic functions of platelets, the cryopreservation process also does not affect their viability rates.